Hak Penuntutan Perserikatan Bangsa-Bangsa Berdasarkan Hukum Internasional - Piternely Matitaputty; Popi Tuhulele; Johanis Steny Franco Peilouw (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: The United Nations (UN) is one of the most important international organizations today. A security officer at the UN representative office in Guzara District, Herat Province when the building became the target of an attack in the middle of a battle between the Taliban militia group and Afghan troops. The purpose of this research is to know and analyze the arrangements for UN employees serving on the territory of member countries according to the UN Charter and to find out whether the UN can legally prosecute the killing of UN employees. The method used is a normative juridical research method using a statutory approach, a conceptual approach as well as a case approach. The results of this study explain that the regulation of cases of murder of UN employees serving in an area is the most important matter according to international law, the UN in this case an international organization must guarantee in upholding the case.